2013
DOI: 10.1083/jcb.201306030
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between Hebbian and homeostatic synaptic plasticity

Abstract: Synaptic plasticity, a change in the efficacy of synaptic signaling, is a key property of synaptic communication that is vital to many brain functions. Hebbian forms of long-lasting synaptic plasticity—long-term potentiation (LTP) and long-term depression (LTD)—have been well studied and are considered to be the cellular basis for particular types of memory. Recently, homeostatic synaptic plasticity, a compensatory form of synaptic strength change, has attracted attention as a cellular mechanism that counterac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
135
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 131 publications
3
135
0
Order By: Relevance
“…With the advent of new, more sensitive tools to both manipulate activity (light-activated channels) and measure activity (voltage-sensitive dyes), these questions will likely be resolved in the near future. Finally, while numerous molecules have been identified to play a role in mechanisms of both types of plasticity, there is an overlap between these molecular cues [93]. The interactions between the molecular mechanisms of Hebbian and homeostatic plasticity are largely unexplored and are an important question for identifying how these different types of plasticity are induced.…”
Section: (D) How Do Mechanisms Interact?mentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of new, more sensitive tools to both manipulate activity (light-activated channels) and measure activity (voltage-sensitive dyes), these questions will likely be resolved in the near future. Finally, while numerous molecules have been identified to play a role in mechanisms of both types of plasticity, there is an overlap between these molecular cues [93]. The interactions between the molecular mechanisms of Hebbian and homeostatic plasticity are largely unexplored and are an important question for identifying how these different types of plasticity are induced.…”
Section: (D) How Do Mechanisms Interact?mentioning
confidence: 99%
“…As a result, predictions from theory to in vivo experiments and viceversa thus far are limited to qualitative aspects. The second focus of experiments is at the molecular and cellular experimental level, where numerous molecular mechanisms have been described to play a role in both homeostatic [17,19,21] and Hebbian [91] plasticity, as well as their interactions [92,93]. While new molecular and systems tools make it easier to link these molecular and cellular mechanisms to in vivo experiments, for example, through the use of Cre-dependent expression of target mechanisms, the brain's redundancy, evidenced by observed compensatory pathways, can make it difficult at times to tease apart the precise roles of individual molecules in the healthy brain.…”
Section: Similarities Across Brain Regions In Vivomentioning
confidence: 99%
“…Modeling studies have shown that when left unchecked, consecutive cycles of synaptic reinforcement or weakening through LTP or LTD should, respectively, lead to runaway excitation or quiescence (Abbott and Nelson 2000;Bienenstock et al 1982;Miller and MacKay 1994;Miller 1996) and eventually impair the ability to encode information. It is now thought that several forms of homeostatic plasticity prevent this from happening (Maffei and Fontanini 2009;Turrigiano and Nelson 2004;Vitureira and Goda 2013;Watt and Desai 2010). Homeostatic plasticity was originally described as a non-Hebbian synaptic plasticity mechanism that maintains an optimal set point of functioning by tuning overall neuronal network activity through negative feedback (Turrigiano et al 1998;Turrigiano and Nelson 2004).…”
mentioning
confidence: 99%
“…During these processes, new synapses can be formed or eliminated and individual regulation of synaptic efficiency is ensured through long-term potentiation (LTP) or long-term depression (LTD) of active synapses. Both mechanisms are Hebbian forms of synaptic plasticity as they promptly reinforce or weaken synaptic efficiency depending on how well the activation of the pre-and postsynaptic neuron correlates (reviewed in Vitureira and Goda 2013). Their associative nature, durability, and input specificity are the essential features that make LTP and LTD ideal cellular correlates of learning and memory formation.…”
mentioning
confidence: 99%
“…It is well established that the strength of communication between excitatory synapses can readily be altered by dynamic changes in the level of neuronal excitation [37]. A persistent increase or decrease in synaptic efficacy is termed long-term potentiation (LTP) or long-term depression (LTD) respectively, and these phenomena are thought to be the key cellular events underlying learning and memory [38][39][40].…”
Section: A Role For Leptin In Regulating Hippocampal Excitatory Synapmentioning
confidence: 99%